1991
DOI: 10.1126/science.1857971
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Effects of a Superantigen in Rheumatoid Arthritis

Abstract: While studying the alpha beta T cell receptor repertoire in rheumatoid arthritis (RA) patients, we found that the frequency of V beta 14+ T cells was significantly higher in the synovial fluid of affected joints than in the peripheral blood. In fact, V beta 14+ T cells were virtually undetectable in the peripheral blood of a majority of these RA patients. beta-chain sequences indicated that one or a few clones dominated the V beta 14+ population in the synovial fluid of individual RA patients, whereas oligoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
225
4
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 620 publications
(249 citation statements)
references
References 42 publications
19
225
4
1
Order By: Relevance
“…In the earlier studies based on detection of Tcr-p chain gene rearrangements by Southern blotting, specific V genes could not be identified. A recent report of Vp use in peripheral blood and synovial fluid of RA patients found that Vpl 4 transcripts were barely detectable in PBMC of four of seven RA patients, but were significantly elevated in synovial fluid (26). However, in the present study Vpl4 transcripts were readily detected in both PBMC and SMC of all patients tested.…”
Section: Discussioncontrasting
confidence: 78%
“…In the earlier studies based on detection of Tcr-p chain gene rearrangements by Southern blotting, specific V genes could not be identified. A recent report of Vp use in peripheral blood and synovial fluid of RA patients found that Vpl 4 transcripts were barely detectable in PBMC of four of seven RA patients, but were significantly elevated in synovial fluid (26). However, in the present study Vpl4 transcripts were readily detected in both PBMC and SMC of all patients tested.…”
Section: Discussioncontrasting
confidence: 78%
“…This model is consistent with a previous model of superantigen-induced RA in humans (14). In that model, the authors proposed that when the V,14-reactive superantigen is introduced into the systemic circulation, clonal deletion of self-reactive V, regions occurs.…”
supporting
confidence: 89%
“…Furthermore, it has been reported that some rheumatoid arthritis (RA) patients exhibit a clonal expansion of T cells in the synovial fluid. These T cells express T cell receptor (TCR) Vp14 (14) and other TCR specificities (14)(15)(16)(17)(18)(19)(20)(21)(22), which suggests that a superantigen(s) might be involved in the development of chronic arthritis. Not all RA patients exhibit a clonal expansion and activation of T cells, however (23,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Microbial antigens, such as mycobacterial antigens and staphylococcal superantigens, may also contribute to T-cell activation in RA. 17,18 However, it is unclear whether T-cell responses to any of these antigens are clinically relevant to RA.…”
Section: Introductionmentioning
confidence: 99%